2011
DOI: 10.1074/jbc.m111.298505
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants of Ubiquitin-CXC Chemokine Receptor 4 Interaction

Abstract: Background: Extracellular ubiquitin functions as a CXC chemokine receptor (CXCR) 4 agonist. Results: Ubiquitin possesses distinct receptor binding and signaling sites and CXCR4 contains separate binding sites for its natural ligands. Conclusion: Ubiquitin mimics the structure-function relationship of chemokines and interacts with CXCR4 through a ligand specific binding site on the receptor. Significance: Agonist-selective pharmacological targeting of CXCR4 appears possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 48 publications
4
53
2
Order By: Relevance
“…Because it has been shown that SDF-1α is predominantly released from bone marrow stromal cells after AMD3100 administration, the finding that coadministration of ubiquitin plus AMD3100 did not influence the AMD3100-induced SDF-1α release in the present study could be explained by insufficient accumulation of ubiquitin in bone marrow (55). On the other hand, it cannot be excluded that ubiquitin functions as a partial or functionally selective CXCR4 agonist in vivo, which could correspond to recent findings suggesting that CXCR4 contains separate binding sites for SDF-1α and ubiquitin (13).…”
Section: Discussioncontrasting
confidence: 33%
See 2 more Smart Citations
“…Because it has been shown that SDF-1α is predominantly released from bone marrow stromal cells after AMD3100 administration, the finding that coadministration of ubiquitin plus AMD3100 did not influence the AMD3100-induced SDF-1α release in the present study could be explained by insufficient accumulation of ubiquitin in bone marrow (55). On the other hand, it cannot be excluded that ubiquitin functions as a partial or functionally selective CXCR4 agonist in vivo, which could correspond to recent findings suggesting that CXCR4 contains separate binding sites for SDF-1α and ubiquitin (13).…”
Section: Discussioncontrasting
confidence: 33%
“…Whereas SDF-1α is a CXCR4 and CXCR7 agonist, ubiquitin is a CXCR4 agonist, but does not bind to CXCR7 (12,13,15,61). Besides being a CXCR4 antagonist, AMD3100 is also a CXCR7 ligand with weak allosteric agonist activity and increases binding of SDF-1α to CXCR7 (62).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we tested the effect of CSB6B in the extracellular space. It has been explored that the extracellular ubiquitin binds to CXCR4 as a ligand and turns on CXCR4 signaling, which results in enhanced AKT expression, AKT phosphorylation, and metastasis [13,31]. In the ubiquitin-CXCR4 signaling process, it is known that hydrophobic residues of ubiquitin including Phe4 and Val70 directly bind CXCR4, and the C-terminal motif facilitates receptor activation [31].…”
Section: Resultsmentioning
confidence: 99%
“…3) that accompanies the separation into (at least) two topological moieties, suggesting that separate receptor docking and effector sites are highly likely on this molecule, thus resembling the structure-function relationships generally observed with chemokines (Saini et al, 2011). Such observations have been made earlier with other CAP proteins of nematodes (Asojo et al, 2005b, Osman et al, 2012, and support the notion that these parasite molecules may act as agonists or ligands for GPCRs such as chemokine receptors, similar to snake and bee toxins that also belong to the CAP superfamily (e.g.…”
Section: Structure Modelsmentioning
confidence: 95%